HPJA special edition introductory comments - Andrew Wilson; Sonia Wutzke (Health Promotion Journal of Australia, 2018)
Issue addressed Fatigue-related driving guidance typically assumes that individuals have sufficient control over sleep and travel decisions to implement recommended strategies. Early parenthood represents a critical exception, characterised by chronic sleep disruption and constrained capacity to avoid driving while fatigued. Despite this, there are limited practical resources available to support safer decision-making in this population. Methods Using a participatory design approach grounded in co-design principles and aligned with the Double Diamond framework, 14 parents of children aged ≤ 5 years completed a workshop and a subsequent survey. This process aimed to inform the co-design of educational resources for new parents by examining experiences of fatigue and fatigued driving, the feasibility of common fatigue management strategies, and preferences for content, format, and delivery of driving safety resources. Results Parents shaped the key content areas, emphasising recognising fatigue, making safer driving decisions when tired, and identifying proactive strategies to reduce fatigue risk that were feasible within the constraints of early parenthood. Participants highlighted the importance of creating brief, easy-to-digest materials. Insights informed the development of a dedicated website (www.safedrivingforparents.com) and seven infographics centred on key domains identified by participants. Conclusions These resources represent an important initial step toward a broader, scalable educational approach that could be delivered in partnership with health services and road safety organisations; however, evaluation is needed to understand their effectiveness in real-world contexts. SO WHAT?: These findings highlight the need for health promotion approaches that prioritise feasible risk-reduction strategies in populations with limited control over sleep and travel demands.